Metal–Semiconductor Field‐Effect Transistors Based on the Amorphous Multi‐Anion Compound ZnON. (3rd March 2020) - Reinhardt, Anna; von Wenckstern, Holger; Grundmann, Marius
Abstract: Electrical properties of metal–semiconductor field‐effect transistors (MESFETs) based on the amorphous n‐type multi‐anion compound zinc oxynitride (ZnON) comprising reactively sputtered platinum as Schottky gate are presented. The Schottky barrier diodes reveal a rectification ratio of 4 × 10 3 at ±2 V and an ideality factor of 1.43. The investigated MESFETs show good switching characteristics with a switching voltage below 2 V, low subthreshold swing of 112 mV dec −1 and reasonable current on/off ratios up to 5 × 10 5 . Additionally, the stability of the devices under visible light illumination is proven. Abstract : The first metal–semiconductor field‐effect transistors (MESFETs) based on amorphous zinc oxynitride (ZnON) are presented. The investigated PtO x /ZnON Schottky gate provides MESFETs with low switching voltage and high field‐effect mobility, making them interesting for flexible low‐voltage and high‐frequency applications.